1984
DOI: 10.1203/00006450-198404001-01895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Breathing Pattern, Sleep States, and Maturation on Functional Residual Capacity (Frc) in Newborn Infants

Abstract: P e d i a t r i c s , Oregon Health Sciences Univ., P o r t l a n d , OR. Moment a n a l y s i s (MA) of MBNW could i n theory be a good method o f q u a n t i f y i n g v e n t i l a t i o n inhomogeneity i n young c h i l d r e n s i n c e i t r e q u i r e s only q u i e t b r e a t h i n g of oxygen f o r <2 minutes and t h e r e s u l t s a r e independent of b r e a t h i n g p a t t e r n o r lung volume. We have developed t h e software r e q u i r e d f o r on-line MA of MBNW and have performed d u p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The O 2 -technique can overestimate FRC by about 10% when the tidal volume is low but is highly reproducible (19). Hence, bearing in mind this systematic overestimation, our overall mean FRC value of 31.2 Ϯ 9.6 mL kg Ϫ1 is within the wide range reported in previous studies (using a variety of other methods) of infants of similar ages and body masses (7,23). Part of the difference with previous studies may result from different techniques and populations.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The O 2 -technique can overestimate FRC by about 10% when the tidal volume is low but is highly reproducible (19). Hence, bearing in mind this systematic overestimation, our overall mean FRC value of 31.2 Ϯ 9.6 mL kg Ϫ1 is within the wide range reported in previous studies (using a variety of other methods) of infants of similar ages and body masses (7,23). Part of the difference with previous studies may result from different techniques and populations.…”
Section: Discussionsupporting
confidence: 66%
“…Although we took care to limit variability, the intrasubject coefficient of variation for FRC was 13.7 Ϯ 11.1%, which corresponds to somewhat lower reproducibility than previously reported with the He technique (8%) (4 ). We failed to observe a sleep state effect on FRC values as previously reported (7,11,23,24), probably because we only measured FRC during regular breathing pattern. In contrast, less recent studies found that the FRC was lower in AS (determined by the behavior and/or from electro-oculograms but without EEG data) (2,10).…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…A large number of studies have reported values for FRC in healthy infants using both helium dilution [23,[26][27][28][29][30][31][32][33] and plethysmographic techniques [34][35][36][37][38][39][40][41][42][43]. Many of these studies have confined measurements to the neonatal period, thereby precluding calculation of prediction equations based on body weight or length.…”
Section: Reference Values In Infantsmentioning
confidence: 99%
“…FRC change with different sleep states has been explored by a number of groups with conflicting results [19][20][21][22][23]. Only STOKES et al [23] explored the concept of FRC variability using the respiratory jacket.…”
mentioning
confidence: 99%